Experimental Study on the Coupled Heat-Moisture-Heavy Metal Pollutant Transfer Process in Soils - Qingke Nie; Wei Wang; Wenkai Guo; Huawei Li (Advances in Civil Engineering)
The coupled physical mechanism of heat conduction, moisture migration, and heavy metal transfer in a kaolin soil was studied by one-dimensional column tests. Two cyclic temperature tests show that, during the second cycle, the temperature close to the heat source of the soil column is lower than that during the first cycle and the temperature far away from the heat source is low, which reflects the influence of heating path. Correspondingly, the moisture content distribution during the second cycle is quite different from that during the first cycle. The higher the soil dry density is, the better the heat conduction is. The lower the dry density is, the more favorable the moisture migration is. The placement direction of the soil column and the set of temperature boundaries affect the moisture distribution of the soil column through the difference in the temperature, gravity, and solid matrix potentials. The temperature-driven liquid water movement effectively promotes the transfer of heavy metal contaminant in unsaturated soils; it is closely correlated with the convection of the heavy metal substances easily dissolved in liquid water. However, the transfer of heavy metal substances in unsaturated soil is not obvious without a thermal driving force. The test results for the different heavy metal ions indicate that the thermally induced transfer distance of the heavy metal pollutants with low adsorption properties (e.g., Cu2+) to soil particles is much larger than that of the heavy metal pollutants with high adsorption properties (e.g., Cd2+).